PENGARUH KONSENTERASI LARUTAN NaOH TERHADAP KUAT TEKAN MORTAR GEOPOLIMER ABU SEKAM PADI - Ema Maria Lestari; Abdi Nasrullah (JURNAL ILMIAH BERING'S, 2021)
Chaff ash waste rice at the process production of rice husk ash. Chaff ash waste rice discared pitches upon. Chaff ash more that evoke because that reason beginning at develops substitution alternative cement chaff ash geopolymer's mortar. Showed that experimental to geopolymer using a mixture of rice husk ash as the original material, NaOH and NaSiO3 as activator, crude aggregate and ground, to determine the effect of differences in morality on the strength of mortar pressure, the age was 3, 7, 14, 21, 28 days. With morality: 12 M, 14M and 16M, with pressing strong result a maximum 28 mortar cement with ratio 1: 1,5 was as big as 15,2 Mpa. T3's sample with concentration 12 m by aged 28 days strength presses maximum be as big as 8,35 Mpa. For T3's sample 14 m with the age 28 days strength presses maximum be as big as 8,35 Mpa, For T3's sample with concentration 16 m with the age 28 days strength presses maximum be as big as 11,33 Mpa. It can be concluded that the maximum pressure strength value of 28 days was at the concentration of NaOH 16 with a Molarity was 11,33 Mpa.